Pengaruh Disiplin Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan Pada PT. Setiajaya Mobilindo Depok - Dio Faqih Saputra; Rani Kurniasari (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
Setiajaya Mobilindo Depok is a Toyota car showroom that sells four-wheeled vehicles for buying and selling to meet human needs. The data collection methods used in this thesis research are questionnaires, observations, and literature reviews. The population consists of 45 employees, and a sample of 45 was determined using the saturated sampling technique, processed using SPSS software version 25. Work discipline and work environment are important factors influencing employee performance. An employee's work discipline is influenced by the work environment and contributes to improving employee performance. PT. Setiajaya Mobilindo Depok should improve work discipline and the work environment to enhance employee performance. The results of this research show that Work Discipline (X1) and Work Environment (X2) have an impact on Employee Performance (Y) at PT. Setiajaya Mobilindo Depok, as evidenced by the t-test results: Work Discipline (4.286 > 2.018) with a probability of 0.000, and Work Environment (3.440 > 2.018) with a probability of 0.662. Simultaneously, the F-value (14.714 > 3.21) with a probability of 0.000.